Spatial distribution of white-handed gibbon calls in relation to forest vertical components, Malaysia, from a perspective of forest management - Okuda, Toshinori; Matsubara, Haruka; Yamada, Toshihiro; Chew, Wei Chuang; Meng, Alvin Shin Lau; Paska, Jacquoelyne; Nishizaki, Hiromitsu; Sidek Omar, Nur Shifatil Ulya; Zakaria, Mohamed (Elsevier, 2022)
The aim of this study was to develop a tool that allows for rapid assessment of arboreal animal distributions. In our acoustic triangulation method, we placed directional microphones atop two canopy towers to get the bearings of calls, allowing us to study the spatial distribution of calling locations of white-handed gibbon (Hylobates lar) within 2400 ha of the Pasoh Forest Reserve in Peninsular Malaysia in relation to three forest vertical components. The calling locations were analyzed in relation to a digital surface model, a digital terrain model, and canopy height (difference between the first two parameters) derived from LiDAR data. The locations where 49 calling points originated were mapped during the survey period (December 2018 to August 2019). All forest vertical components at the calling locations were significantly higher than the average values over the whole study site, which suggests that white-handed gibbons choose taller canopy trees at locations with higher elevation. Topographically convex areas (ridgetops or upper hillslopes) tended to be chosen as calling locations over concave areas (e.g., valleys, lower slopes). In addition, calling locations were concentrated in primary forest rather than in regenerating forest, where the canopy height was shorter and more structurally homogeneous than in the primary forest. Based on these results, we mapped the area of high probability for gibbon calling locations by compiling the four parameters of forest vertical components using principal component analysis. This map based on the vertical aspects of vegetation can be helpful in properly managing the forest for gibbon conservation, enabling a rapid assessment of land-use plans within a geographic area where the calling locations occur with high probability.